A DEVELOPMENT PROCESS OF NO-BURNING IN AGRICULTURAL SOCIETY: A SUCCESS OF PEOPLE’S PARTICIPATION IN PHAYAO, THAILAND - Raksi, Kiattibutra; Bunyarit, Sinkangam (PEOPLE: International Journal of Social Sciences, 2020)
It was strongly confirmed that the burning of biomass caused pollution and was harmful to the environment. This research aimed to develop an efficient process of people’s participation to reduce burning agricultural waste in the society of Phayao, Thailand. It was also to study the impact of people's participation in integrated farming to reduce smog. The research areas were 3 different types where more hotspots were reported. The data was collected by interviewing, questioning, and group discussions through 393 participants from three villages. Descriptive statistics were used for the analysis of data. An application of appropriate cropping system patterns in integrated farming was also used for field research to replace the actual planting of field corn and upland rice. The development method started with people concurrence and cultivating the purposed crops such as sweet corn, chilly, and beans associated with major crops for one year. It was found that there were good yields in all 3 areas. The productive efficiency of each crop assessment presented 77% of farmers cultivated both upland rice and specialty corns. In terms of creating community participation principles and social responsibility concepts, the sample groups emphasized participation in preventing and solving smog and forest fires as a whole at a high level ( =4.17). The result revealed people’s positive attitude in decision making and participation in research activities at the highest level. However, the sample groups agreed at a moderate level to avoid burning agricultural materials ( =3.40). It was recommended that community leaders should increase their roles of communicating information to the community, especially the campaign of community philosophy to jointly solve the problems.